Association between periodontitis and fibrotic progression of non‐alcoholic fatty liver among Japanese adults. (19th January 2021) - Kuroe, Kei; Furuta, Michiko; Takeuchi, Kenji; Takeshita, Toru; Suma, Shino; Shinagawa, Takashi; Shimazaki, Yoshihiro; Yamashita, Yoshihisa
Abstract: Aim: Non‐alcoholic fatty liver (NAFL) is known to develop into liver fibrosis, which increases the risk of liver cirrhosis and liver cancer. The association between periodontal condition and fibrotic progression of NAFL is unclear. This study aimed to clarify this longitudinal association. Materials and Methods: Among 4812 participants aged 35–64 years undergoing annual health check‐ups between 2003 and 2004, and follow‐up 5 years later, 392 participants were diagnosed with NAFL. After excluding participants with liver fibrosis at baseline, 341 participants were followed up for 5 years. NAFL disease fibrosis score of ≥−1.455 was used to evaluate the probability of the presence of liver fibrosis. Results: During the follow‐up period, 10.6% of participants progressed to liver fibrosis. A higher clinical attachment level (CAL) tended to be associated with the incidence of liver fibrosis in the logistic regression analysis (odds ratio [OR] 1.82, 95% confidence interval [CI], 0.94–3.49, p = .074). The stratified analysis by obesity revealed a significant association with higher CAL in obese participants (OR 2.87, 95% CI, 1.23–6.69, p = .015), but not in non‐obese participants. Conclusion: Higher CAL was associated with an increased probability of liver fibrosis in obese adults with NAFL.